Forest assisted migration and adaptation plantings in the Northeastern US: perspectives and applications from early adopters - Clark, Peter W.; D’Amato, Anthony W.; Fitts, Lucia A.; Janowiak, Maria K.; Montgomery, Rebecca A.; Palik, Brian J. (Frontiers in Forests and Global Change, 2024)
Threats to the future function of forested ecosystems and stability of ecosystem service provisioning due to global change have motivated climate-adaptive forest management strategies that include various forms of tree planting termed “adaptation plantings”. Despite the emergence of these strategies, less is known as to how foresters and other natural resource managers perceive or are engaged with adaptation plantings like forest assisted migration (FAM). This knowledge gap is most pronounced in regions like New England and the North Central US (hereafter, the Northeastern US) where tree planting is less common but expected to be an important forest management tool for adaptation. To address this, we surveyed 33 natural resource managers in this region actively engaged in climate change adaptation (i.e., early adopters of the practice) to assess how tree planting for adaptation is currently being pursued against the perceived barriers, opportunities, and potential future engagement with the strategy. Survey respondents overwhelmingly (93.5%) forecast increases in the future use of adaptation plantings in their work in the region, attributed to increased awareness, acceptance, and interest in the practice. Respondents expressed notable interest in strategies related to diversification and most types of FAM (e.g., assisted population expansion and assisted range expansion), but hesitancy to engage with more contentious planting types like afforestation or FAM linked to the long-distance translocation of exotic species (e.g., assisted species migration). Although examples of local enrichment plantings (i.e., non-FAM) proliferate, nineteen of the top twenty most common tree genera planted contain at least one example of FAM in the study region. The most notable barriers reported were themed as 1) biotic and abiotic, 2) information and material, and 3) policy, social, and economic factors. While most respondents report difficulty obtaining adequate planting material from nurseries (i.e., seedlings), over 80% placed orders shortly before planting (< 1 year) which likely generates difficulty in sourcing seedlings suited for a specific site and future range of environmental conditions. Although this study is limited by focusing on subset of natural resource managers who are early adopters of climate change adaptation within the region, valuable inferences into the barriers and trends are possible from this population serving on the front lines of forest adaptation. Together, these results from early adopters suggest a potentially growing need for allocating resources that engage forest stewards in adaptation planning and serve to refine policy, financing, and management practices to support this adaptation strategy in this region and beyond.